Hubungan Kecerdasan Emosional Dengan Perilaku Bullying Siswa Kelas VIII UPTD SMP Negeri 16 Kupang Tahun Pelajaran 2024/2025 - Nanga, Natalia Twignarti Alfilia; Lejap, Gracianus Edwin Tue. P.; Bone, Matilda Pia (Program Studi Bimbingan dan Konseling FKIP UMSU, 2025)
This study aims to analyze the relationship between emotional intelligence and bullying behavior among eighth-grade students at SMP Negeri 16 Kupang in the 2024/2025 academic year. The research employed a quantitative approach with a descriptive-correlational method. The sample consisted of 41 students selected through simple random sampling from a total population of 163 students. Research instruments included an emotional intelligence questionnaire with 39 valid items (α = 0.784) and a bullying behavior questionnaire with 50 valid items (α = 0.845). Data were analyzed using Pearson’s Product-Moment correlation test at a 5% significance level. The findings showed that most students had moderate levels of emotional intelligence (49%) and moderate levels of bullying behavior (46%). The correlation test yielded r = -0.458 with a significance value of 0.003 (p 0.05), indicating a significant negative relationship between emotional intelligence and bullying behavior. This means that the higher the students’ emotional intelligence, the lower their tendency to engage in bullying. These results highlight the importance of developing emotional intelligence through counseling services, character education, and collaboration between teachers, parents, and schools to create a safe, inclusive learning environment that supports students’ positive development.